PSYCHOLOGICAL AND ORGANIZATIONAL BASIS OF THE “ECONOMIC MAN” PARADIGM REPRODUCTION - Mirzoyan, V. A.; Martirosyan , A. R. (Արդի հոգեբանություն, 2019)
The article is devoted to the analysis of the essence and manifestations of the “economic man” paradigm. Ideas about the behavior of “economic man”, formed as a managerial paradigm in the late 19th – early 20th centuries, constantly reproduced under the influence of certain psychological factors and in certain organizational forms.